Meningkatkan Legalitas Produk Melalui Pendampingan untuk Pengurusan Ijin Edar dan Sertifikasi Halal pada UMKM Kusuma Sari - Kusumaningrum, Ine Febri; Zakia, Iqna Faridhatuz; Saadah, Irfaus; Natalia, Jian; Putra, Jonathan Rizki Eka; Mauludin, M. Soleh (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to increase the legality of Kusuma Sari MSME products through assistance in processing distribution permits and halal certification. It is hoped that this assistance can help Kusuma Sari MSMEs located on Jl. Kusuma Nation Hero No. 18A, Kediri City, fulfill halal requirements and strengthen their business development strategy. The method used in this service involves IAIN Kediri students who provide guidance and consultation regarding halal production practices, selection of raw materials, and production processes according to halal standards. Apart from that, assistance also includes developing marketing strategies that emphasize halal certification to increase product attractiveness in local and international markets. The results of this service activity show that Kusuma Sari MSMEs have succeeded in adopting halal production practices that comply with standards, obtaining halal certification, and increasing product legality. As a result, the competitiveness of products in the market increases, and Kusuma Sari MSMEs are able to attract more consumers both locally and internationally.